Kulturni transfer - Kuster, Helena (Jezik in slovstvo, 2008)
The influence of the German linguistic-cultural sphere on the Slovene sphere is also evident in the field of phraseology. In the present article we focus on that part of phraseological lexical units in Slovene language whose direct connection with German culture is most easily demonstrated. These are phrases derived from citations from canonised German authors and their literary works,which also retain their canonic status in a diachronic sense in the Slovene cultural sphere. The habituation of cited phrases and their exploitations is clear proof of the fact that they are deeply rooted in the collective consciousness. The comparability of appearances in both of the linguistic-cultural spheres from a synchronous perspective demonstrates the transfer on the model level.
Keywords: frazeologija; German; German-language literature; jezikovni vplivi; kulturni vplivi; nemščina; nemška književnost; phraseology; prevajanje; Slovene; slovenščina; translation